The Nationwide Landscape of K–12 School Websites in the United States: Systems, Services, Intended Audiences, and Adoption Patterns - Kimmons, Royce; Hunsaker, Enoch W.; Jones, J. Evan; Stauffer, McKell (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
This study sought to collect URLs (web addresses) of all K-12 schools in the United States (N = 98,477) and analyze website home page system and service data for all available U.S. institutional websites (n = 65,899). Building upon previous research related to Web 2.0 educational potentials, this first-of-its-kind study sought (a) to provide descriptive results of system and service adoption and website data for all schools in the United States and (b) to detect theorized differences based upon school demographics and service/system type (e.g., open source vs. proprietary). Results indicated that proprietary and purchased systems were much more common than free and open systems, that adoption patterns were generally not meaningfully influenced by demographic data (except for charter school status), and that K-12 institutional adoption of Web 2.0 seems to be more focused on educational uses of these tools that might not strictly be considered pedagogical (e.g., community outreach).